The First Book of Jewish Jokes : The Collection of L. M. Büschenthal - Büschenthal, Lippmann Moses, 1784-1818 (Book collections on Project MUSE., 2018)
"Works on Jewish humor and Jewish jokes abound today, but what formed the basis for our contemporary notions of Jewish jokes? How and when did these perceptions develop? In this groundbreaking study and translation, noted humor and folklore scholar Elliott Oring introduces us to the joke collections of Lippmann Moses Büschenthal, an enlightened rabbi, and an unknown author writing as "Judas Ascher." Originally published in German in 1812 and 1810, these books include jokes and anecdotes that play on stereotypes. The jokes depict Jews dealing with Gentiles who are bent on their conversion, Jews encountering government officials and institutions, newly propertied Jews attempting to demonstrate their acquisition of artistic and philosophical knowledge, and Jews engaged in trade and moneylending--often with the aim to defraud. In these jokes we see the antecedents of modern Jewish humor, and in Büschenthal's brief introduction we find perhaps the earliest theory of the Jewish joke. Oring provides helpful annotations for the jokes and contextualizing essays that examine the current state of Jewish joke scholarship and the situation of the Jews in France and Germany leading up to the periods when the two collections were published. Intended to stimulate the search for even earlier examples, Oring challenges us to confront the Jewish joke from a genuine historical perspective."--Back cover.